The year 1968 in the memory of one generation - Vrzgulová, Monika (Traditiones (Ljubljana), 2013)
The paper presents initial findings of research carried out among a same-age cohort (respondents born between the years 1938-1950) in the same town. The objective was to collect biographical narratives concerning the lives of the youth in the 1960s. The paper focuses on interpretations of respondents' leisure time activities within a chosen urban area and their reflections on the invasion of the town on the part of occupation armies.
Keywords: ethnology; Etnologija; Življenjske zgodbe; Biografska metoda; Način življenja; Mladina; Czech Republic; Češka; Slovaška; 1968; ljudsko življenje